Birds N.Am. 2018
DOI: 10.2173/bna.tribla.03.1
|View full text |Cite
|
Sign up to set email alerts
|

Tricolored Blackbird (Agelaius tricolor)

Abstract: Breeding range of the Tricolored Blackbird in California. Overall outline of the range is stable, though numbers of breeders have declined dramatically. Colonies typically are largest in the Central Valley and are patchily distributed throughout, but particularly in the Coast Ranges and on the coastal slope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Our genome‐wide analyses also illustrate higher and more far‐reaching vagility by tricoloreds than previously known, though multiple studies employing bands on thousands of individuals have revealed large‐scale movements over major portions of the breeding range. These include, for instance, across the Central Valley (Beedy et al., 2018; DeHaven et al., 1975; Neff, 1942), along the coast (Wilson et al., 2016), and throughout southern California (Neff, 1942). However, because movements were not observed between the Central Valley and southern California, in particular by Neff (1942), the prevailing notion was that tricoloreds should be considered two separate demes split between these areas.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our genome‐wide analyses also illustrate higher and more far‐reaching vagility by tricoloreds than previously known, though multiple studies employing bands on thousands of individuals have revealed large‐scale movements over major portions of the breeding range. These include, for instance, across the Central Valley (Beedy et al., 2018; DeHaven et al., 1975; Neff, 1942), along the coast (Wilson et al., 2016), and throughout southern California (Neff, 1942). However, because movements were not observed between the Central Valley and southern California, in particular by Neff (1942), the prevailing notion was that tricoloreds should be considered two separate demes split between these areas.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, beyond the aforementioned biological causes, there is also an analytical component that should be considered. Our current N e calculation may be reduced by the presence of overlapping generations (Waples et al., 2014), which is likely in our dataset because adults are long‐lived (~12 years) and a lack of variation in molt and plumage beyond the second year limits age assessments (Beedy et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations